Concentrated micro choice-based treatment for type 2 diabetes is associated with decreased risk of sleep apnoea, less daytime sleepiness and lower insomnia symptoms. A non-randomized pre – post pilot study - Wilhelmsen-Langeland, Ane; Olson, Karsten Amund; Kjøde, Markus Rød; Hystad, Sigurd William; Kvale, Gerd; Søfteland, Eirik (Frontiers in Sleep, 2025)
AimsType 2 diabetes and sleep disorders are closely connected. We have evaluated a 4-day concentrated transdiagnostic, micro choice-based and interdisciplinary group treatment for patients with type 2 diabetes, with the aim of improving patient activation. We wanted to explore whether sleep problems would decrease after this intervention.MethodsPatients were assessed pre – post the intervention by Insomnia Severity Index (ISI), Bergen Insomnia Scale (BIS), Epworth Sleepiness Scale (ESS), Berlin Questionnaire (BQ) at baseline, 3-, 6- and 12 months follow-up, to measure symptoms related to insomnia, Obstructive Sleep Apnoea (OSA) and daytime sleepiness. Seventy-five patients with type 2 diabetes were included in our sample.ResultsAt baseline, 41% and 25% had symptoms of insomnia, as defined by the BIS and ISI, respectively. Another 56% were likely to suffer from OSA using the BQ. At follow-up, the intervention was associated with reduction in symptoms of sleep disorders, and the reduction was still significant at 12 months follow-up.ConclusionsAlthough the study was not designed to disentangle how much of the improvement was due to sleep education and medication, the outcome still shows the usefulness of the format also in terms of sleep disorders in type 2 diabetes.